Pengembangan Lembar Kerja Anak Berbasis Bahasa Ibu Bagi Peningkatan Pra-Literasi Di Kober Peupado - Fono, Yasinta Maria; Ita, Efrida; Odo, Maria Efrasia; Ngole, Kristina; Ninu, Marselina (As-Sibyan: Jurnal Pendidikan Anak Usia Dini, 2024)
This research aims to develop mother tongue-based children's worksheets to improve the pre-literacy aspects of early childhood in PAUD in Golewa District. The limited availability of teaching materials that utilize children's worksheets is one of the challenges faced by teachers in teaching children, who are generally more familiar with their mother tongue than Indonesian. This research uses development research with the ADDIE model, which consists of five stages: analysis, design, development, implementation and evaluation. The research results show that mother tongue-based children's worksheets can increase children's interest in learning and make it easier for them to understand the material. It is hoped that these findings can contribute to improving the quality of pre-literacy aspects in early childhood in Ngada district